2022
DOI: 10.3390/cells11172750
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Antagonists Mitigate Mitral Regurgitation-Induced Myocardial Dysfunction

Abstract: Mitral regurgitation (MR), the disruption of the mitral valve, contributes to heart failure (HF). Under conditions of volume overload, excess mineralocorticoids promote cardiac fibrosis. The mineralocorticoid receptor antagonist spironolactone is a potassium-sparing diuretic and a guideline-recommended therapy for HF, but whether it can ameliorate degenerative MR remains unknown. Herein, we investigate the efficacy of spironolactone in improving cardiac remodeling in MR-induced HF compared with that of a loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…A number of preclinical studies have shown MR overactivation in cardiac dysfunction. 32 , 33 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…A number of preclinical studies have shown MR overactivation in cardiac dysfunction. 32 , 33 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%